Induction chemotherapy by cisplatin, 5-FU and leucovorin versus cisplatin and 5-FU followed by chemoradiotherapy in locally advanced head and neck cancer - Sumsuzoha, A. Z. M.; Arifeen, Muhammad Adnan; Haque, M. Ershadul; Sweet, Ahammad Al Mamun; Bhuiyan, M. Ruhul Amin; Bayzid, Khandakar Rezwan; Alam, M. Nazmul (International Journal of Research in Medical Sciences, 2025)
Background: Head and neck squamous cell carcinoma (HNSCC) is a prevalent malignancy in Bangladesh, with many patients presenting in advanced stages. The study aimed to compare the therapeutic efficacy and safety profile of induction chemotherapy using Cisplatin, 5-fluorouracil (5-FU), and Leucovorin versus Cisplatin and 5-FU followed by chemoradiotherapy in patients with locally advanced HNSCC. Methods: This quasi-experimental study was conducted at KYAMCH over 18 months, involving 80 patients divided into two treatment arms. Arm A received ICT with Cisplatin and 5-FU followed by CRT; Arm B received Cisplatin, 5-FU and Leucovorin followed by CRT. Results: 80 patients were evenly randomized into Arm A and Arm B, with comparable baseline characteristics (mean age ~52 years, predominantly male, and similar ECOG performance status; all p>0.05). Tumor and disease profiles showed no significant differences between groups (all p>0.05), with Stage IVA and moderately differentiated tumors being most common. After induction chemotherapy, partial response was the predominant outcome in both arms, while complete response rates were higher in Arm B (27.5% vs. 17.5%), but this difference was not statistically significant (p=0.550). Longitudinal assessment at 6, 12, and 24 weeks showed increasing complete response rates in both arms, peaking at 24 weeks (60.0% Arm A, 65.0% Arm B), with no significant differences at any timepoint (p>0.85). Conclusion: Both treatment arms showed comparable efficacy and safety, with slightly higher complete response rates and toxicity in the arm receiving chemoradiotherapy. No statistically significant differences were observed.